2018
DOI: 10.3390/agriculture8070092
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Bamboo Leaf on the Growth of Pyricularia grisea Fungus

Abstract: Abstract:In this study, the effects of bamboo leaf were examined on mycelial growth of Pyricularia grisea, a fungus of rice blast disease that causes a great loss in rice production. The hexane extract exhibited maximal reduction on growth of P. grisea (IC 50 = 0.62 mg/mL), followed by aqueous and ethyl acetate extracts, while the methanol extract was least effective (IC 50 = 9.71 mg/mL). At 0.5-1.0 mg/mL doses, all extracting solvents showed inhibition on the growth of P. grisea, but at a 0.1 mg/mL concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…aqueous roots, leaves and outer culms producing mean ZOI of 0.00 mm). The findings mentioned may also be correlated a previous study result wherein it was observed that phytocomponents from the leaf extracts of bamboo species Phyllostachys and Moso bamboo are not water soluble (38). However, the presence of polar phytocompounds in the different parts of B. blumeana could not be totally eliminated from the current study since aqueous extracts also exhibited zones of inhibitions against the previously discussed fungal species.…”
Section: Variations In the Antifungal Property Of Bambusa Blumeana (Kawayang Tinik) Against Penicillium Chrysogenumsupporting
confidence: 90%
See 2 more Smart Citations
“…aqueous roots, leaves and outer culms producing mean ZOI of 0.00 mm). The findings mentioned may also be correlated a previous study result wherein it was observed that phytocomponents from the leaf extracts of bamboo species Phyllostachys and Moso bamboo are not water soluble (38). However, the presence of polar phytocompounds in the different parts of B. blumeana could not be totally eliminated from the current study since aqueous extracts also exhibited zones of inhibitions against the previously discussed fungal species.…”
Section: Variations In the Antifungal Property Of Bambusa Blumeana (Kawayang Tinik) Against Penicillium Chrysogenumsupporting
confidence: 90%
“…Specifically, apigenin and tricin derivatives were noted to be abundant in the root and leaf part of the said bamboo species. Antifungal mechanisms of these identified phytocompounds were noted to be fungal membrane and metabolic disruption (38,39) the same inhibitory action of fluconazole, a standard antifungal drug (28).…”
Section: Variations In the Antifungal Property Of Bambusa Blumeana (Kawayang Tinik) Against Penicillium Chrysogenummentioning
confidence: 99%
See 1 more Smart Citation
“…The chemicals identified by GC-MS in the methanol extract were mostly from the bamboo leaf. But they were inactive on the growth of P.grisa with all concentrations (Toan et al 2018). In this experiment, P.grisea was inhibited by methanol extract ( Table 5).…”
Section: Discussionmentioning
confidence: 62%
“…Several other trees were tested and showed P. grisea inhibition (Olufolaji et al 2015, Netam et al 2011. In other research, the composition of bamboo leaves containing compounds derived from hexane and ethyl acetate such as fatty acids, oils and phenols, and their derivatives minimize the growth of P. grisea (Toan et al 2018).…”
Section: Introductionmentioning
confidence: 99%